2005
DOI: 10.1152/ajpheart.00001.2005
|View full text |Cite
|
Sign up to set email alerts
|

The scar neovasculature after myocardial infarction in rats

Abstract: series of novel techniques, adapted from the field of tumor biology, were developed to quantify vascular structure and function and to explore the role of ANG II receptor AT1 in cardiac remodeling after myocardial infarction (MI). We examined the scar neovasculature at 1-4 wk post-MI in SpragueDawley rats with a view toward its ability to deliver and exchange oxygen. CD31 and DiOC 7(3) staining was used to visualize anatomical vessels vs. those perfused. EF5/Cy3 immunohistochemical staining was used to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…Negative and positive controls for the presence of phosphoSmad2 consisted of lysates of AML12 cells treated with vehicle or TGF-␤1 (21). 3 Samples were resolved by SDS-polyacrylamide gel electrophoresis on 10% gels and transferred to polyvinylidene difluoride membranes in 25 mM Tris, 192 mM glycine, 5% methanol at 85 V for 3 h at 4°C. Filters were blocked overnight with TBS-T (10 mM Tris-HCl, pH 7.4, 150 mM NaCl, 0.05% Tween 20) containing 5% skim milk.…”
Section: Methodsmentioning
confidence: 99%
“…Negative and positive controls for the presence of phosphoSmad2 consisted of lysates of AML12 cells treated with vehicle or TGF-␤1 (21). 3 Samples were resolved by SDS-polyacrylamide gel electrophoresis on 10% gels and transferred to polyvinylidene difluoride membranes in 25 mM Tris, 192 mM glycine, 5% methanol at 85 V for 3 h at 4°C. Filters were blocked overnight with TBS-T (10 mM Tris-HCl, pH 7.4, 150 mM NaCl, 0.05% Tween 20) containing 5% skim milk.…”
Section: Methodsmentioning
confidence: 99%
“…Also consistent with our findings are the reports of Walther et al (34), who showed that AT 1 inhibits angiogenesis in a mouse alginate implant angiogenesis model, and de Boer et al (5), who showed that post-MI microvessel density is reduced in transgenic rats overexpressing AT 1 in the heart and that the reduction in microvessel density is reversed by the AT 1 blocker losartan. Very recently, Wang et al (35) have shown by a new technique that losartan significantly restored vascular perfusion in a 4-wk-old infarct scar in rat hearts and suggested AT 1 as being antiangiogenic. The difference may partly result from the fact that the effect on angiogenesis is strongly dependent on the model.…”
Section: Effect Of At 1a On Granulation Tissue Cell Dynamics and Its mentioning
confidence: 99%
“…Thus, this is the minimal time necessary to reliably exclude contrast enhancement of intravascular agents. The relatively slow transport of intravascular Gd-chelates shown in this and previous studies can be explained by: 1) microvascular obstruction (37,38), 2) high gradient pressure in the interstitium due to edema (9,37), and 3) slow convection process compared with passive diffusion transport (9,12,13,36). In a previous study (8), changes in SI on T 1 -weighted spin echo MRI and histopathology were correlated in acute, subacute, and chronic infarctions.…”
Section: Discussionmentioning
confidence: 50%
“…Because the distribution volume and mechanism of distribution of intravascular and extracellular MR contrast agents differ considerably (9,10), the enhancement pattern in acute myocardial infarctions (AMIs) and chronic infarctions might also be different. This seems likely because vascular integrity is destroyed in acutely infarcted myocardium but is intact in scar tissue (11)(12)(13)(14). The hypothesis of the current study was that intravascular Gd-chelates produce delayed contrast enhancement of acute but not chronic MIs.…”
mentioning
confidence: 83%